Trends in Violation of the Notary Code of Ethics in Indonesia - Mustiqo Vitra Ardhiansyah; Jusuf Irianto; M. Hadi Shubhan (Enrichment : Journal of Management, 2022)
Notaries are public officials who have a big responsibility to the community in terms of making authentic deeds. Notary in carrying out activities to act professionally by complying with the code of ethics of the Notary position. However, the fact is that violations of the code of ethics still often occur which makes the image of the Notary tarnish. Describe the forms of violations of the Notary code of ethics in Indonesia for the last 5 (five) years. This research is a qualitative research with data collection methods through the study of SINTA indexed journals that violate the code of ethics violations committed by a Notary and then analyzed using qualitative data analysis. The forms of violations of the code of ethics committed by Notaries in Indonesia during the last 5 (five) years consist of planned violations (planned violations) originating from the wishes of the Notary himself and unplanned violations (unplanned violations) which originate from the Notary's fault. . Notaries who commit violations make Notaries unprofessional, because they do not carry out their duties according to their responsibilities and as stated in the Notary's code of ethics.